The rheology of caramel - Barra, Giuseppina (2004)
The rheology of caramel was determined as a function of processing temperature and hydrocolloid additions. As the processing temperature increased the water content decreased and the caramel viscosity increased. X-ray diffraction showed that although crystalline fat was present, for the most part the sugars were in the amorphous state. The exception was the lowest water content caramel (7.9% water w.w.b.) which had been processed to a temperature of 122ºC. This had a small amount of crystalline fructose. Caramel rheology was assessed by rotational and capillary rheometry. Rotational rheometry gave information on the steady shear viscosity, the dynamic parameters (storage and loss moduli and related functions) and the creep compliance and recovery response. Capillary rheometry gave shear viscosities at high shear rates and an extensional viscosity. It was found that caramel without added hydrocolloids had behavior which was close to a Newtonian liquid. The only exception to this was the values obtained for the Trouton ratio which ranged from 10 to 40. This was considerably higher than the value of 3 for a Newtonian fluid and may reflect the difficulties in making measurements on these relatively low viscosity systems in the capillary rheometer. The viscosities obtained from steady shear, oscillation and creep were combined and three approaches were used to model the data as a function of measurement temperature and water content. An empirical statistical model using a second order polynomial, an Arrhenius fit and a Williams Landel Ferry (WLF) model. The former and the latter gave a good fit to the data although the constants used in the WLF model varied with the water content of the caramel. Arrhenius plots showed curvature particularly at low water contents.